Teachers and Students of Abu Isa Tirmidhi - Temirov Kabiljonovich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
In the article, the years of birth and death of Abu Isa Tirmidhi, when he went on a journey of knowledge and in which cities he visited, his famous teachers, the number of sheikhs and hadiths narrated the most in "Sunnan Tirmidhi", 10 prominent students, dates of death, full name and brief information about himself.